2014
DOI: 10.1371/journal.pone.0089255
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Sexual Attraction of Spodoptera frugiperda Corn- and Rice-Strain Males to Pheromone Lures

Abstract: The corn- and rice-strains of Spodoptera frugiperda exhibit several genetic and behavioral differences and appear to be undergoing ecological speciation in sympatry. Previous studies reported conflicting results when investigating male attraction to pheromone lures in different regions, but this could have been due to inter-strain and/or geographic differences. Therefore, we investigated whether corn- and rice-strain males differed in their response to different synthetic pheromone blends in different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 77 publications
3
72
0
2
Order By: Relevance
“…Wind tunnel and field tests demonstrated that Z7,9‐10:OH markedly increased the number of attracted M. flavescens males in the Chinese population, when the compound was added to the sex pheromone mixtures. Isomers of a pheromone component are usually critical for attracting males, as shown for the two pheromone strains of Ostrinia nubilalis (Hübner) (Lassance, ; Unbehend et al., ). If we added Z9,11‐12:OH to the pheromone blend, it resulted in a marked synergistic effect in the wind tunnel and field tests.…”
Section: Discussionmentioning
confidence: 99%
“…Wind tunnel and field tests demonstrated that Z7,9‐10:OH markedly increased the number of attracted M. flavescens males in the Chinese population, when the compound was added to the sex pheromone mixtures. Isomers of a pheromone component are usually critical for attracting males, as shown for the two pheromone strains of Ostrinia nubilalis (Hübner) (Lassance, ; Unbehend et al., ). If we added Z9,11‐12:OH to the pheromone blend, it resulted in a marked synergistic effect in the wind tunnel and field tests.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the sex pheromone components of China populations of H. robusta were different from other regions. However, the phenomenon of (Qingyuan, Guangdong, China, 2014) insect sex pheromone variation is universal, such as Hemileuca electra (McElfresh and Millar 1999), Hyphantria cunea (Su et al 2008), genus Adoxophyes (Yang et al 2009), Cydia strobilella (Wang et al 2010), Spodoptera frugiperda (Unbehend et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pheromone races in moths are sometimes associated with different host plants, for example in the European corn borer Ostrinia nubilalis (Leppik and Frerot, 2012;Unbehend et al, 2014). In comparison, pheromone races in C. splendana demonstrate that separate pheromone communication channels alone can account for premating isolation, despite overlapping host use and geographical distribution.…”
Section: Interaction Of Pheromones and Plant Volatilesmentioning
confidence: 99%
“…However, the EZ/EEpheromone blend of C. splendana from Swedish oak forests did not attract males in chestnut plantations in France. Host races of several moths, including European corn borer, fall armyworm and larch budmoth are known to use different pheromone blends (Guerin et al, 1984;Leppik and Frerot, 2012;Unbehend et al, 2014). This led us to reinvestigate the sex pheromone of C. splendana from chestnut, showing that C. splendana uses two different pheromone blends that probably contribute to reproductive isolation.…”
Section: Introductionmentioning
confidence: 99%